Streamlining breast cancer and colorectal cancer biosimilar regulations to improve treatment access in Latin America: an expert panel perspective. Issue 7 (July 2022) - Teran, Enrique; Gomez, Henry; Hannois, Damian; Lema, Mauricio; Mantilla, William; Rico-Restrepo, Mariana; McElwee, Elizabeth; Castro Sanchez, Noe; Valdivieso, Natalia; Espinoza, Manuel Antonio
Summary: In a multiday conference, a panel of Latin American experts in biological cancer therapies and health economics were provided with questions to address the barriers restricting access to biosimilars in Latin America, specifically for patients with breast cancer and colorectal cancer, for whom biosimilars can be a path forward to increasing access to care. During the conference, responses were discussed and edited until a consensus was achieved. The regulatory challenges identified in the conference included heterogenous regulations, non-adherence to regulatory pathways, scarcity of market opportunity, inadequate naming of biosimilars by only using international non-proprietary names, imprecise use of interchangeability and substitution, and insufficient traceability and pharmacovigilance. Recommendations were developed to improve the implementation of regulatory pathways and reliable procurement strategies that increase access to these therapies with adequate traceability and outcome measures; efforts from all involved stakeholders will be crucial. These recommendations can serve as a strategy for biosimilar adoption in other countries in a similar situation.